The impacts of intellectual property rights protection on cross-border M&As - Iftekhar Hasan; Fahad Khalil; Xian Sun (Bank of Finland, 2017)
We investigate the impacts of improved intellectual property rights (IPR) protection on cross-border M&A performance. Using multiple measures of IPR protection and based on generalized difference-in-differences estimates, we find that countries with better IPR protection attract significantly more hi-tech cross-border M&A activity, particularly in developing economies. Moreover, acquirers pay higher premiums for companies in countries with better IPR protection, and there is a significantly higher acquirer announcement effect associated with these hi-tech transactions.
URN:NBN:fi:bof-201708071456
Keywords: G32; G34; O31; O34; F43; C23; 330